Emergency Ocular Ultrasound – Common Traumatic and Non-Traumatic Emergencies Diagnosed with Bedside Ultrasound - Hoffmann, Beatrice; Schafer, Jesse M.; Dietrich, Christoph F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Point-of-care ocular ultrasound (POCOUS) in the ambulatory and critical care setting has become an invaluable diagnostic tool for patients presenting with traumatic or atraumatic vision and ocular complaints. Sonographic bedside evaluation is intuitive and easy to perform and can accurately diagnose a variety of pathologies. These include detachment or hemorrhage of the retina or vitreous, lens dislocation, retrobulbar hematoma or air, as well as ocular foreign bodies, infections, tumors, and increased optic nerve sheath diameter that can be assessed in the setting of suspected increased intracranial pressure. The ocular anatomy is easy to visualize with sonography, as the eye is a superficial structure filled with fluid. Over the last two decades, a large number of scientific publications have documented that POCOUS in emergent or critical care settings is an accurate diagnostic tool and expands and improves emergency diagnosis and management. This article will review POCOUS exam techniques as well as normal sonographic findings and common pathologies.Der okuläre Point-of-Care-Ultraschall (POCOUS) hat sich im ambulanten und intensivmedizinischen Bereich zu einer unschätzbaren diagnostischen Methode für Patienten mit traumatischen oder nichttraumatischen Sehstörungen und Augenbeschwerden entwickelt. Die sonografische Auswertung am Krankenbett ist intuitiv und einfach durchzuführen und kann eine Vielzahl von Pathologien genau diagnostizieren. Dazu gehören Ablösung oder Blutung der Netzhaut oder des Glaskörpers, Linsenluxation, retrobulbäres Hämatom oder Luft sowie Fremdkörper des Auges, Infektionen, Tumoren und ein erhöhter Durchmesser der Sehnervenscheide, die bei Verdacht auf einen erhöhten Hirndruck beurteilt werden können. Die Anatomie des Auges ist mit der Sonografie leicht zu visualisieren, da das Auge eine oberflächliche Struktur ist, die mit Flüssigkeit gefüllt ist. In den letzten 2 Jahrzehnten wurde in zahlreichen wissenschaftlichen Publikationen dokumentiert, dass POCOUS in der Notfall- oder Intensivmedizin ein treffsicheres diagnostisches Verfahren ist und die Notfalldiagnose und -behandlung erweitert und verbessert. In diesem Artikel werden POCOUS-Untersuchungsmethoden sowie normale sonografische Befunde und häufige Pathologien beschrieben.